2022
DOI: 10.1186/s40813-022-00278-7
|View full text |Cite
|
Sign up to set email alerts
|

Blood metabolic and physiological profiles of Bama miniature pigs at different growth stages

Abstract: Background Bama miniature pigs aged between six (6 M) and twelve months (12 M) are usually used in human medical research as laboratory pigs. However, the difference in serum metabolic profiles from 6 to 12 M-old pigs remains unclear. This study aimed to identify the metabolic and physiological profiles present in the blood to further explain changes in Bama miniature pig growth. We collected blood samples from 6 M-, eight-month- (8 M-), ten-month- (10 M-), and 12 M-old healthy Guangxi Bama min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…The Bama miniature pig is a local pig breed in Southern China, characterized by excellent reproductive performance, strong disease resistance, and tender meat. Research has shown that the Bama miniature pig has a newborn weight of about 450 g, reaches sexual maturity at 90-120 days of age, and weighs up to 40 kg as an adult pig [6]. Because of its small size, rapid growth and development, and easy feeding management, it is a principal experimental animal model.…”
Section: Introductionmentioning
confidence: 99%
“…The Bama miniature pig is a local pig breed in Southern China, characterized by excellent reproductive performance, strong disease resistance, and tender meat. Research has shown that the Bama miniature pig has a newborn weight of about 450 g, reaches sexual maturity at 90-120 days of age, and weighs up to 40 kg as an adult pig [6]. Because of its small size, rapid growth and development, and easy feeding management, it is a principal experimental animal model.…”
Section: Introductionmentioning
confidence: 99%